2013
DOI: 10.1371/journal.pone.0056920
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterisation of Colour Formation in the Prawn Fenneropenaeus merguiensis

Abstract: IntroductionBody colouration in animals can have a range of functions, with predator protection an important aspect of colour in crustaceans. Colour determination is associated with the carotenoid astaxanthin, which is taken up through the diet and stabilised in the tissues by the protein crustacyanin. As a variety of genes are found to play a role in colour formation in other systems, a holistic approach was employed in this study to determine the factors involved in Fenneropenaeus merguiensis colouration.Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 67 publications
1
24
0
Order By: Relevance
“…However, CRCN gene expression did not vary across the moult cycle or in response to substrate colour (Wade et al 2012). Albino colour morphs of shrimp (Fenneropenaeus merguiensis) displayed significantly reduced expression of the CRCN-A and C genes compared with other shrimp, as well as a range of other genes potentially involved in the regulation of crustacean colour (Ertl et al 2013). However, expression levels of CRCN were not significantly different between light-and dark-coloured shrimp, and there was no correlation between levels of CRCN gene expression and Axn content (Ertl et al 2013).…”
Section: Carotenoproteins and Crustacyaninmentioning
confidence: 98%
See 1 more Smart Citation
“…However, CRCN gene expression did not vary across the moult cycle or in response to substrate colour (Wade et al 2012). Albino colour morphs of shrimp (Fenneropenaeus merguiensis) displayed significantly reduced expression of the CRCN-A and C genes compared with other shrimp, as well as a range of other genes potentially involved in the regulation of crustacean colour (Ertl et al 2013). However, expression levels of CRCN were not significantly different between light-and dark-coloured shrimp, and there was no correlation between levels of CRCN gene expression and Axn content (Ertl et al 2013).…”
Section: Carotenoproteins and Crustacyaninmentioning
confidence: 98%
“…At present, two genes that encode CRCN-A and CRCN-C have been identified across a range of crustaceans (Wang et al 2007;Wade et al 2009;Ertl et al 2013). Their expression is restricted to the outer layer of the hypodermis (Wang et al 2007;Wade et al 2009), and the spatial regulation of the CRCN genes is thought to define the speciesspecific shell colours and patterns that different crustaceans display (Wade et al 2009).…”
Section: Carotenoproteins and Crustacyaninmentioning
confidence: 99%
“…Color is one of the most important visual properties for consumers in seafood, especially in shrimps . Normally, changes in shrimp color during different preservation conditions were quantified by determination of L* (lightness / darkness), a* (redness / greenness) and b* (yellowness / blueness).…”
Section: Physicochemical Analysismentioning
confidence: 99%
“…Color is one of the most important visual properties for consumers in seafood, especially in shrimps. [89][90][91] Normally, changes in shrimp color during different preservation conditions were quantified by determination of L* (lightness / darkness), a* (redness / greenness) and b* (yellowness / blueness). Zhang et al (2015) reported that the L* values of raw L. vannamei tended to decrease and b* values tended to increase after 16 days of icing storage.…”
Section: Physical Indexes Colormentioning
confidence: 99%
“…Crustaceans cannot synthesize carotenoids and must obtain them from their diets (Goodwin 1952), whether that be from natural pond biota or supplemented in aquaculture feeds. In shrimp, colour can be enhanced by different dietary supplementation regimes from various carotenoid sources (summarized in Wade, Gabaudan & Glencross 2015), but is also influenced by light intensity (You, Yang, Liu, Liu, Zhou & Zhang 2006), genetics (Ertl, Elizur, Brooks, Kuballa, Anderson & Knibb 2013), background colour (Tume, Sikes, Tabrett & Smith 2009) or combinations of these factors (Wade, Budd, Irvin & Glencross 2015). Strong consumer preference for highly pigmented shrimp fetch premium prices in some markets (Shahidi, Metusalach & Brown 1998;Erickson, Bulgarelil, Resurreccion, Vendetti & Gates 2007;Parisenti, Beirão, Tramonte, Ourique, da Silveira Brito & Moreira 2011).…”
Section: Introductionmentioning
confidence: 99%